1999
DOI: 10.1055/s-2008-1034747
|View full text |Cite
|
Sign up to set email alerts
|

Okuläre Bakteriose bei einem Patienten mit aplastischer Anämie

Abstract: The histologic results in our patient displayed numerous bacilli without inflammatory reaction which was a result of the aplastic state. Therefore, this disease was classified as "ocular bacteriosis". The blood-ocular barrier undergoes direct assault with intraocular inflammation and the impermeability to blood-borne antibiotics is lost. However, with the lack of an inflammatory reaction the permeability to antibiotics may be too low and the achieved concentration insufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In 18 cases of aplastic anemia, Mansour et al (2000) reported preretinal hemorrhages in 67%, cotton wool spots in 38%, nerve fiber layer and vitreous hemorrhage in 13%, and optic disc edema in 6%. Ocular neovascularization (Yahia et al, 2006), macular hemorrhage (Sudhir et al, 2002), and ocular bacteriosis (Spraul et al, 1999) have all been previously associated with aplastic anemia.…”
Section: Commentmentioning
confidence: 99%
“…In 18 cases of aplastic anemia, Mansour et al (2000) reported preretinal hemorrhages in 67%, cotton wool spots in 38%, nerve fiber layer and vitreous hemorrhage in 13%, and optic disc edema in 6%. Ocular neovascularization (Yahia et al, 2006), macular hemorrhage (Sudhir et al, 2002), and ocular bacteriosis (Spraul et al, 1999) have all been previously associated with aplastic anemia.…”
Section: Commentmentioning
confidence: 99%